(untitled) (Journal of Accessibility and Design for All, 2025)
Interaction design is the act of designing the dialogue between people and systems, services or products. User interface (UI) facilitates sensory and emotional interactions by acting as a bridge between users and products while graphical user interface (GUI) refers to graphical or visual presentations of information The accessibility of GUIs directly impacts the quality of experience (QoE) since the sense of sight plays a pivotal role especially for low vision users throughout the interaction process. Though low vision users can use GUIs on their own, they often face challenges that hinder their QoE. Although existing research has explored accessible UI design principles, studies specifically addressing the accessibility issues of low vision users in GUI interactions remain limited. The goal of this research is to evaluate the effects of visual perception differences between people with low and normal vision on home appliances’ GUI interactions and discuss how these differences affect the QoE of low vision users. To this end, we created a total of 12 washing machine GUI cases based on the GUI model of the best-selling washing machine in Turkey in 2021 and tested these cases online with two groups of 7 participants each with low vision and normal vision. The results infer that low vision participants have accessibility issues on GUIs in terms of colour contrasts, text sizes, display options and control panel distances. The study suggests that using an uppercase larger font (22pt) for just the first syllable of the text in text-based displays can improve accessibility of GUIs for low vision users compared to using the same font size (16pt) in sentence case for all text. Overall, this study contributes to a better understanding of the challenges faced by low vision users in GUI interactions and offers practical recommendations for creating more accessible GUIs through a display style proposal.